A mesoporous cationic thorium-organic framework that rapidly traps anionic persistent organic pollutants. Issue 1 (December 2017) - Li, Yuxiang; Yang, Zaixing; Wang, Yanlong; Bai, Zhuanling; Zheng, Tao; Dai, Xing; Liu, Shengtang; Gui, Daxiang; Liu, Wei; Chen, Meng; Chen, Lanhua; Diwu, Juan; et al.
Abstract Many environmental pollutants inherently exist in their anionic forms and are therefore highly mobile in natural water systems. Cationic framework materials that can capture those pollutants are highly desirable but scarcely reported. Here we present a mesoporous cationic thorium-based MOF (SCU-8) containing channels with a large inner diameter of 2.2 nm and possessing a high surface area of 1360 m2 g−1 . The anion-exchange properties of SCU-8 were explored with many anions including small oxo anions like ReO4 − and Cr2 O7 2− as well as anionic organic dyes like methyl blue and the persistent organic pollutant, perfluorooctane sulfonate (PFOS). Both fast uptake kinetics and great sorption selectivity toward PFOS are observed. The underlying sorption mechanism was probed using quantum mechanical and molecular dynamics simulations. These computational results reveal that PFOS anions are immobilized in SCU-8 by driving forces including electrostatic interactions, hydrogen bonds, hydrophobic interactions, and van der Waals interactions at different adsorption stages. Cationic metal-organic frameworks provide promising opportunities to capture anionic pollutants, but stable frameworks with sufficiently large pores are lacking. Here the authors present a thorium-based mesoporous, cationic and hydrolytically-stable MOF that can rapidly trap inorganic and organic anionic pollutants.